2003
DOI: 10.3354/dao057247
|View full text |Cite
|
Sign up to set email alerts
|

Risk of inter-river transmission of Gyrodactylus salaris by migrating Atlantic salmon smolts, estimated by Monte Carlo simulation

Abstract: The possibility of Gyrodactylus salaris infection of wild North Atlantic salmon Salmo salar spreading to new rivers poses a major threat in Norway. This freshwater parasite can survive for some time in brackish water, and it has been suggested that smolts leaving infected rivers could transport vital parasites to new rivers. A Monte Carlo simulation model was used to estimate the risk that infected smolts would ascend a new river. Data from an infected watercourse in Norway, where the salmon population is main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…G. salaris was recorded on experimental fish after more than 200 h at 10 ‰ salinity and 72 h at 15 ‰ salinity, and 37 out of 52 Atlantic salmon smolts caught 25 km from the outlet of the River Drammenselva were infected with up to 1105 G. salaris specimens (Soleng & Bakke 1997, Soleng et al 1998. Risk assessment studies of fjord-wise dispersal pathways to salmon rivers near to the River Drammenselva estimated an annual risk of 31% for the event that at least one infected salmon smolt would enter the River Sandeelva (Høgåsen & Brun 2003). G. salaris readily transmits to a wide range of both salmonid and non-salmonid host species, suggesting that a range of species may serve as short-term transport hosts for the parasite (Bakke et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…G. salaris was recorded on experimental fish after more than 200 h at 10 ‰ salinity and 72 h at 15 ‰ salinity, and 37 out of 52 Atlantic salmon smolts caught 25 km from the outlet of the River Drammenselva were infected with up to 1105 G. salaris specimens (Soleng & Bakke 1997, Soleng et al 1998. Risk assessment studies of fjord-wise dispersal pathways to salmon rivers near to the River Drammenselva estimated an annual risk of 31% for the event that at least one infected salmon smolt would enter the River Sandeelva (Høgåsen & Brun 2003). G. salaris readily transmits to a wide range of both salmonid and non-salmonid host species, suggesting that a range of species may serve as short-term transport hosts for the parasite (Bakke et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, an interesting case is the River Sandeelva in Region 1, with a relatively low predicted probability (0.39) of infection in the present study. The risk-assessment conducted by Høgåsen & Brun (2003) concluded that the risk of inter-river dispersal of G. salaris on migrating fish from the River Drammenselva to the River Sandeelva was high, but that their analysis was sensitive to assumptions with regard to salinity in the fjord area covering the dispersal pathway. Incidentally, G. salaris was recorded in the River Sandeelva in 2003, 16 yr after G. salaris was recorded in the River Drammenselva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low water concentration of parasites also indicates that the probability of attachment of drifting parasites to immersed equipment or swimmers is low. In comparison, the risk of inter-river transmission of G. salaris by migrating Atlantic salmon smolts or other species could be significant (Høgåsen & Brun 2003, Peeler et al 2004). All results support the hypothesis by Jansen et al (2007) that G. salaris dispersal in Norway is due to either anthropogenic movement of infested salmon, or migration of infested salmon in fjord systems.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Høgåsen & Brun (2003), it was assumed that the sensitivity (Se) of the diagnostic method used by Soleng et al (1999a) was most likely 0.95, with a minimum value of 0.9 and a maximal value of 1, i.e. 90 to 100% of the fish infested by Gyrodactylus salaris were detected.…”
Section: Methodsmentioning
confidence: 99%